PERAN BUDAYA RASA MALU DAN RASA BERSLAH DALAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Anisah Nur Azizah; Hanna Yasmin Shupaeroh; Meidira Rachel Trisyahrani; Putri Gita Lestari; Hotijah, Siti; Al-Adawiyah, Rabbiah; Nawawi, Muhammad Azhar; Yatri, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore the role of shame and guilt culture in character education in elementary schools. The research method used was a literature study by analyzing journals related to shame culture, guilt culture, and character education. The results showed that shame culture tends to emphasize the importance of self-image and social acceptance, while guilt culture emphasizes individual conscience and internal moral principles. This difference affects various aspects of people's lives, including in the context of character education in elementary schools. Shame culture can encourage students to behave in accordance with social norms to avoid shame, while guilt culture can encourage students to behave ethically and responsibly based on conscience and moral principles. The implication of this finding is the need to pay attention to cultural aspects in the implementation of character education in primary schools so that it can be more effective and appropriate to the local context